2017
DOI: 10.1158/1078-0432.ccr-17-1789
|View full text |Cite
|
Sign up to set email alerts
|

The Driver Mutational Landscape of Ovarian Squamous Cell Carcinomas Arising in Mature Cystic Teratoma

Abstract: We sought to identify the genomic abnormalities in squamous cell carcinomas (SCC) arising in ovarian mature cystic teratoma (MCT), a rare gynecological malignancy of poor prognosis. We performed copy number, mutational state, and zygosity analysis of 151 genes in SCC arising in MCT ( = 25) using next-generation sequencing. The presence of high-/intermediate-risk HPV genotypes was assessed by quantitative PCR. Genomic events were correlated with clinical features and outcome. MCT had a low mutation burden with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 22 publications
5
40
1
Order By: Relevance
“…[19,23] On the contrary, Cooke et al found no SCC was positive for HPV in their 25 cases. [20] In our case, we also can find diffusely positive for p16 in immunohistochemical staining while her was HPV negative. More validation studies were needed to explore whether HPV might have acted as the root cause for the malignant transformation in OMCT.…”
supporting
confidence: 60%
“…[19,23] On the contrary, Cooke et al found no SCC was positive for HPV in their 25 cases. [20] In our case, we also can find diffusely positive for p16 in immunohistochemical staining while her was HPV negative. More validation studies were needed to explore whether HPV might have acted as the root cause for the malignant transformation in OMCT.…”
supporting
confidence: 60%
“…Squamous cell carcinoma (SCC) is the most common histological type in malignant transformation of MCT [1,3], which is reasonable because skin epithelium is usually found in MCT [4]. Recently, Cooke et al analyzed genomic alterations of 25 SCCs arising from MCT (MCT-SCC) by using a gene panel with 151 cancer-related genes and reported frequent alterations of TP53, PIK3CA, and CDKN2A that are also frequently detected in other types of SCC [5]. However, the number of targeted genes in their study was limited, and other molecular characteristics of MCT-SCC such as transcriptome, proteome, and methylation profiles remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently altered genes in SCC were TP53 (20/25 cases, 80%), PIK3CA (13/25 cases, 52%) and CDKN2A (11/25 cases, 44%). [20] In the study done by Iwasa et al, [21] overexpression of the p53 protein was observed in 67% SCC cases (14 in 21 cases), while four of them had point mutations in the p53. In humans, p16 is encoded by the CDKN2A gene.…”
Section: Gene Mutation In Omctsmentioning
confidence: 93%